Harmonizing and supporting infection control training in Europe. Issue 4 (April 2015) - Brusaferro, S.; Arnoldo, L.; Cattani, G.; Fabbro, E.; Cookson, B.; Gallagher, R.; Hartemann, P.; Holt, J.; Kalenic, S.; Popp, W.; Privitera, G.; Prikazsky, V.; et al.
Summary: Healthcare-associated infection (HCAI), patient safety, and the harmonization of related policies and programmes are the focus of increasing attention and activity in Europe. Infection control training for healthcare workers (HCWs) is a cornerstone of all patient safety and HCAI prevention and control programmes. In 2009 the European Centre for Disease Prevention and Control (ECDC) commissioned an assessment of needs for training in infection control in Europe (TRICE), which showed a substantial increase in commitment to HCAI prevention. On the other hand, it also identified obstacles to the harmonization and promotion of training in infection control and hospital hygiene (IC/HH), mostly due to differences between countries in: (i) the required qualifications of HCWs, particularly nurses; (ii) the available resources; and (iii) the sustainability of IC/HH programmes. In 2013, ECDC published core competencies for infection control and hospital hygiene professionals in the European Union and a new project was launched ['Implementation of a training strategy for infection control in the European Union' (TRICE-IS)] that aimed to: define an agreed methodology and standards for the evaluation of IC/HH courses and training programmes; develop a flexible IC/HH taxonomy; and implement an easily accessible web tool in 'Wiki' format for IC/HH professionals. This paper reviews several aspects of the TRICE and the TRICE-IS projects.